Physical Test Training as a Part of Preventive Health Equipment Maintenance in Puskesmas Ciledug, Tangerang City - Hermawan, Frisa Yugi (Universitas Pendidikan Ganesha, 2020)
Health equipment is one of the most important supporting factors in the implementation of health services in health service facilities. The condition and function of health equipment must be good and can support health services. The Ciledug Public Health Center (Puskesmas Ciledug) in Tangerang City has an electromedical device that requires regular maintenance. This activity aimed to provide a correct understanding of the inspection and preventive maintenance (IPM) of electromedical devices to operators/users in the electrical sector, which was oriented towards habits (routine) as a preventive activity before the equipment is damaged and can extend the life of the electromedical device. The used methods were presentation, discussion, practice, and functional tests to the devices. The expected results were to be input to improve the ability of users/operators in handling IPM and build an understanding related to a culture of caring for maintenance to the top Management of Puskesmas Ciledug.